Cum-cives, ie citizens of the polis, and urban policy - Stefano Aragona (European Regional Science Association (ERSA), 2016)
Objectives The issues of happiness and well-being of the citizens are central in the work of urban planners and land planners . This is the purpose of their existence in the modern city , as considered , for example by Franco Pure from the sixteenth century. The same Athens' Charta drawn up in the 30s of ' 900 was created with these objectives. For several decades the market has taken more and more space, because the policy has pull back itself and has left to the economy the decisive role in the planning, and therefore also in social choices. The paper aims to highlight the socially and spatially devastating outcomes, also environmentally, of those choices. Then it suggests urban policies that, instead, can be effective and not only efficient ones Methods, techniques, modes of inquiry, data sources Following the phenomenological philosophy, the paper carries out quantitative and qualitative analysis is of some concrete cases, differentiated by size and location. Eg. in Rome while there are 50,000 people (of a total population of 2,880,000 inhabitants approx) with housing needs, 110,000 housing unities are empty. It is clear that there is a disequilibrium either social that physical. But there is also a qualitative study, using tools such as eg. the Fair and Equitable Wellbeing and (BES) proposed by ISTAT-CNEL alongside those suggested by the Charter of Quality by AUDIs (Association of Urban Disused Areas) since 2007. These two instruments put emphasis on the need to confront the issues addressed in a multidisciplinary way, so with a multicriteria, 'integrated', approach. In a broader perspective that goes back to '"human ecology". School of thought that has the two cosentin philosophers, ie Bernardino Telesio (with the "Philosophy of Nature") and his disciple Thomas Campanella (the author of "The City of the Sun"), as fathers in the modern age and then the various thinkers of Anglo-Saxon origin as H.D. Thoreau, W. Whitman, then I.L. McHarg, P. Soleri etc. the latest references. References that are the basis of the goals of the EU strategies. These are declared and evident, as example, in "Smart City" (2007) where it is said that the goal is to buold local Communities, inclusive and sustainable, either materially and socially. An important element of the study is the time, because the land use decisions have consequences often do not revealed immediately. This means test the effects in the short, medium, and long period. Conclusions The paper, having highlighted the gaps and inconsistencies of the actual philosophy of action, essentially based on the market, thanks to the mention of "best pratices" proposes a different path. Highlighting the benefits and conditions necessary to ensure that the policy, and therefore the planning of territories and cities, goes back to being effective and therefore useful: that is to be the art of managing the polis for its citizens, its cum-cives
Keywords: 330